A longitudinal approach to disentangle how conscientiousness creates happy people: The mediating role of self-leadership and the moderating role of perceived leadership effectiveness - Junça Silva, A.; Camaz, A. (Heliyon, 2023)
This study relied on the conservation of resources model to explore the interaction between individual differences (conscientiousness and behavior-focused self-leadership) and contextual factors (perceived leadership effectiveness) to predict well-being. Using results from a three-wave longitudinal study of working adults (N = 107*3 = 321, mean age = 46.05 years, 54% male), we examined: (1) the indirect effect of conscientiousness on well-being via behavior-focused self-leadership; and (2) the moderating role of perceived leadership effectiveness on the indirect effect. The multilevel results showed that conscientiousness influenced well-being through behavior-focused self-leadership over time. The results also showed that the indirect effect was moderated by perceived leadership effectiveness, in such a way that it became stronger when individuals had leaders perceived as less effective (versus more effective). Thus, behavior-focused self-leadership seems to be a process through which conscientiousness influences well-being; when conscientiousness was lower there was an increase behavior-focused self-leadership when the leader was perceived as effective; this contextual need decreased as conscientiousness increased. That is, it seems that when there is something external regulating the individual, s/he feels less need to self-regulate. The results highlight the role of personal (conscientiousness), cognitive (behavior-focused self-leadership) and contextual resources (perceived leadership effectiveness) for well-being.